Neutrino Oscillations in the Atmospheric Parameter Region: From the Early Experiments to the Present - G. Giacomelli; M. Giorgini; L. Patrizii; M. Sioli (Advances in High Energy Physics)
The aim of this paper is to provide a historical perspective on the main experimental steps which led to the current picture of neutrino oscillations in the “atmospheric parameter region.” In the 1980s a deficit of atmospheric muon neutrinos was observed with the first generation of underground experiments. In the following decade new experiments provided fundamental results which led to the discovery claims in 1998. At the beginning of the new century neutrino beams of medium and high energy became available and several long baseline experiments were performed and added new information to the atmospheric neutrino puzzle. The interpretation of the results of atmospheric and long baseline neutrino experiments was in terms of dominant νμ→ντ oscillations. Short recollections are made of the SNO solar neutrino measurements, of the results with neutrino telescopes, and of reactor neutrinos to measure sin2θ13. Over the years the phenomenological picture improved in completeness and increased in complexity. A short perspective concludes the paper.